Top dog [compact disc, unabridged] : the science of winning and losing - Bronson, Po, 1964- (Hachette Audio, 2013)
An analytical and scientific look at the nature of competition and what is required to be the 'Top Dog.' Authors Po Bronson and Ashley Merryman argue that while people are still competitive nowadays, they compete for futile and useless goals and are daunted by the prospect of true competition. They offer an analysis on how to be a true competitor, and how to ultimately become 'Top Dog.'